PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL KOOPERATIF TPS ( THINK, PAIR, SHARE ) DENGAN MEDIA WORDWALL DI KELAS V SDN 100/II MUARA BUNGO - Dicka septia putri.b; Puput wahyu hidayat; Aldino (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This Classroom Action Research was conducted on fifth-grade students at SDN 100/II Muara Bungo due to the low learning outcomes caused by the underdevelopment of students' scientific processes, as evident from the average mathematics test scores. Out of 28 students, only 10 were categorized as having achieved mastery, while 18 others were categorized as not having achieved mastery. This research aims to describe the improvement in the process and outcomes of mathematics learning using the Cooperative Model TPS (Think, Pair, Share) with Wordwall Media in Class V SDN 100/II Muara Bungo.This Classroom Action Research was conducted on fifth-grade students at SDN 100/II Muara Bungo due to the low learning outcomes caused by the underdevelopment of students' scientific processes, as evident from the average mathematics test scores. Out of 28 students, only 20 were categorized as having achieved mastery, while 8 others were categorized as not having achieved mastery. This research aims to describe the improvement in the process and outcomes of mathematics learning using the Cooperative Model TPS (Think, Pair, Share) with Wordwall Media in Class V SDN 100/II Muara Bungo.The research results show that: 1) the learning process of students using the TPS (Think, Pair, Share) cooperative model with Wordwall media in cycle I reached 36% with a poor category, increasing to 86.00% in cycle II with a very good category, 2) the teaching process by teachers using the TPS model with Wordwall media increased from 70% in cycle I to 95% in cycle II, 3) students' mathematics learning outcomes improved in each cycle, from 52% to 89%. It can be concluded that the application of the TPS (Think, Pair, Share) model with Wordwall media can increase student activeness and cooperation, thereby developing their scientific process and improving the achievement of student learning outcomes.